2011
DOI: 10.3748/wjg.v17.i30.3518
|View full text |Cite
|
Sign up to set email alerts
|

Stomach cancer screening and preventive behaviors in relatives of gastric cancer patients

Abstract: The gastric cancer screening and preventive behaviors of GCRs have yet to be improved. To increase awareness among GCRs, systematic family education programs should be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…A recent meta-analysis of five studies showed that family history can exert beneficial effects in gastric cancer patients [77]. Subjects undertake frequent health screenings due to their family history of gastric cancer [78], show good health-related behaviors, such as non-smoking, non-alcoholic drinking and consistent exercise, and frequently have microsatellite instability and mismatch repair proteins, which are associated with a good prognosis [73]. …”
Section: Effect Of Family History On the Outcome Of Gastric Cancermentioning
confidence: 99%
“…A recent meta-analysis of five studies showed that family history can exert beneficial effects in gastric cancer patients [77]. Subjects undertake frequent health screenings due to their family history of gastric cancer [78], show good health-related behaviors, such as non-smoking, non-alcoholic drinking and consistent exercise, and frequently have microsatellite instability and mismatch repair proteins, which are associated with a good prognosis [73]. …”
Section: Effect Of Family History On the Outcome Of Gastric Cancermentioning
confidence: 99%
“…Such a system may be particularly useful in identifying early gastric cancer where endoscopic findings are unreliable and histological analysis may not distinguish gastric-type differentiated lesions from regenerative or inflammatory changes. First-degree relatives (FDRs) of gastric cancer patients are considered to be at risk of developing future disease, presumably due to a genetic susceptibility and possibly due to common environmental exposures [6][7][8][9]. The mucin phenotype of the gastric mucosa in healthy FDRs has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications in high risk behavior is essential in primary prevention of gastric cancer (Kang et al, 2011 ). Many studies have demonstrated an association between unhealthy food (i.e.…”
Section: Discussionmentioning
confidence: 99%